Economic effect of modification the optimal contour of the Open Pit South Mining District Majdanpek, Republic of Serbia - Kržanović Daniel; Rajković Radmilo; Gomilanović Miljan; Stanić Nikola; Doderović Aleksandar (Mining and Metallurgy Engineering Bor, 2024)
The Open Pit South Mining District is a unique unit that operates within the company Copper Mine Majdanpek, which is a part of the company Serbia Zijin Copper doo (former Mining and Smelting Basin Bor Group). The capacity of the Open Pit is 9.9 million tons per year and is of a great importance for copper production in the company system. As a result of natural and technical factors, a landslide occurred on the Eastern side of the open pit, so it became necessary to define a new final contour of the open pit. In this paper, the effect of modification the optimal contour of the Open Pit South Mining District on the net present value (NPV) was analyzed.